(untitled) (CIPEEX, 2024)
CHILDHOOD OBESITY IS A DISEASE CHARACTERIZED BY AN INCREASE IN BODY FAT. IT IS CURRENTLY TREATED AS ONE OF THE MAJOR PUBLIC HEALTH PROBLEMS WORLDWIDE WITH A SIGNIFICANT IMPACT ON POPULATION HEALTH, AS IT CAN LEAD TO CHRONIC NON-COMMUNICABLE DISEASES SUCH AS SYSTEMIC ARTERIAL HYPERTENSION (SAH), TYPE 2 DIABETES MELLITUS (T2DM), AND CARDIOVASCULAR DISEASES. IN BRAZIL, IT IS PRESENT IN DIFFERENT SOCIOECONOMIC GROUPS, BEING MORE COMMON IN THE UPPER SOCIAL CLASS. THIS CONDITION IS INFLUENCED BY SOCIOECONOMIC STATUS THROUGH INCOME, EDUCATION, AND OCCUPATION AND RESULTS IN SPECIFIC BEHAVIORAL PATTERNS THAT CAN AFFECT METABOLIC RATE, CALORIC INTAKE, AND ENERGY EXPENDITURE. OBESITY CAN BE DEFINED AND CLASSIFIED AS EXCESS FAT IN ALL BODY REGIONS, WHICH CAN BE CAUSED BY POOR EATING HABITS, ENDOCRINE-METABOLIC DISORDERS, OR GENETIC ALTERATIONS. OVERWEIGHT CAN OCCUR AT ANY STAGE OF AN INDIVIDUAL’S LIFE, BUT IT MAINLY APPEARS IN THE FIRST YEAR OF LIFE, BETWEEN 5 AND 6 YEARS OF AGE, AND DURING ADOLESCENCE. HOWEVER, INTERVENTION SHOULD BE CARRIED OUT AT ANY STAGE OF LIFE TO PREVENT COMPLICATIONS ARISING FROM EXCESS WEIGHT. THIS STUDY AIMS TO PROVIDE A THEORETICAL REFLECTION ON CHILDHOOD OBESITY AND IDENTIFY THE GENERAL ASPECTS ASSOCIATED WITH THIS CONDITION, HIGHLIGHTING EPIDEMIOLOGICAL, ETIOLOGICAL, CONSEQUENCES, AND TREATMENT ASPECTS, CONSIDERING THE IMPORTANCE OF PHYSICAL ACTIVITY. IT IS A LITERATURE REVIEW CONDUCTED IN THE SCIELO AND GOOGLE SCHOLAR DATABASES, WITH STUDIES RANGING FROM 2018 TO 2023. IT CAN BE CONCLUDED THAT CHILDHOOD OBESITY IS CURRENTLY A SERIOUS PUBLIC HEALTH PROBLEM WORLDWIDE. THERE ARE SEVERAL FACTORS THAT CAN LEAD TO OVERWEIGHT, INCLUDING GENETIC FACTORS, POOR NUTRITION, AND SEDENTARY LIFESTYLE. THEREFORE, THE MANAGEMENT AND PREVENTION OF CHILDHOOD OBESITY ARE IMPORTANT, AS IT CAN BE EASILY CONTROLLED IN THE VAST MAJORITY OF CASES THROUGH CHANGES IN EATING HABITS AND INCREASED PHYSICAL EXERCISE. IT IS KNOWN THAT OBESITY IS RELATED TO VARIOUS COMPLICATIONS AND INCREASED CHILDHOOD MORBIDITY AND MORTALITY, AS WELL AS IN THE ADULT AGE GROUP. THEREFORE, IT IS OF UTMOST IMPORTANCE TO MAKE AN ACCURATE DIAGNOSIS AND PROVIDE PROPER TREATMENT, AS WELL AS TO IMPLEMENT PUBLIC POLICIES FOR THE PREVENTION OF CHILDHOOD OBESITY.